SISTEM REKOMENDASI TEMPAT RENTAL MOBIL DI JOMBANG MENGGUNAKAN METODE SMART (SIMPLE MULTI ATTRIBUTE RATING TECHNIQUE) BERBASIS WEB - Fathoni , Annas; Zein Vitadiar , Tanhella (Inovate, 2023)
Car rental services in Jombang are still very rare compared to areas with many other newcomers, such as in Kampung Inggris located in Pare, Kediri. Therefore, many students and university students have difficulty finding car rental locations that meet their desired criteria. From this issue, the development of a car rental place recommendation system using the SMART (Simple Multi Attribute Rating Technique) method is one solution and also a utilization of technology in the current global era where time efficiency is highly sought after. The SMART method is frequently used due to its simplicity in responding to decision-makers' needs and analyzing responses. The criteria used are service, car model, car year, 12-hour rental price, and 24-hour rental price. Alternative data was obtained from surveys conducted by the author to find car rental places and surveys conducted with customers. The results of this study show that in the SMART method, the values assigned to the weights determine the most effective recommendations, with this study focusing on emphasizing the criterion of the cheapest price. The results of this study also indicate that using the SMART method can assist customers in choosing one of the best rental places in the Jombang area, particularly in the Diwek, Megaluh, and Perak districts. Keywords: Recommendation System, SMART, Car Rental.